2021
DOI: 10.1051/e3sconf/202123202008
|View full text |Cite
|
Sign up to set email alerts
|

Improving Pigmented Rice Farmers' Marketing Activity for Sustainable Agroindustry: Consumers' Voice to be Considered

Abstract: The demand for pigmented rice is highly increasing due to the consumer changing on a healthy lifestyle. The price of pigmented rice is higher than white rice, so it may be an opportunity to improve farmers' welfare. However, as producers, the farmers said they understand the consumer's needs and wants. They lack access to consumers' information. This article attempted to reveal the consumers' perspective of pigmented rice in Indonesia through their preferences and perceived quality. Those are variables indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, the demand for pigmented rice is increasing due to the consumer changing to a healthy lifestyle. As producers and traders, they understand the consumer's needs and wants, they lack access of consumers' information [19]. Some customers preferred to buy imported rice because it was cheaper than locally-produced rice [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, the demand for pigmented rice is increasing due to the consumer changing to a healthy lifestyle. As producers and traders, they understand the consumer's needs and wants, they lack access of consumers' information [19]. Some customers preferred to buy imported rice because it was cheaper than locally-produced rice [20].…”
Section: Discussionmentioning
confidence: 99%
“…Wuryandani's survey showed that consumers are willing to buy at a premium even though they do not like the taste or texture of pigmented rice. They continue to consume the product's superiority of its nutritional content, which affects their health [35]. Perlinger's research shows that consumers are willing to pay more for premium products that include labels and health benefits [36].…”
Section: Purchase Intention For Pigmented Ricementioning
confidence: 99%
“…Promotional activities through advertising media aim to influence and convince consumers of pigmented rice by emphasizing information on organic farming and pigmented rice cultivation systems that do not harm the environment so that consumers become interested and decide to buy organic pigmented rice. Promotion media attractive to pigmented rice consumers are advertisements, health-related campaigns, and information on the packaging [35]. Organic agriculture is an environmentally friendly agricultural system without chemicals that damage the balance of the environment and utilizes local resources [39], [40].…”
Section: Purchase Intention For Pigmented Ricementioning
confidence: 99%